Effect of basicity in the aqueous phase reforming of brewery wastewater for H2 production. (April 2020) - Oliveira, A.S.; Baeza, J.A.; Garcia, D.; Saenz de Miera, B.; Calvo, L.; Rodriguez, J.J.; Gilarranz, M.A.
Abstract: Real (RBW) and synthetic brewery wastewater (SBW) were treated by aqueous phase reforming (APR) with different 3%Pt/C catalysts for H2 production from the biomass-derived organic load. APR enabled simultaneous treatment of the wastewater and valorisation to H2 and alkanes of the biomass-derived organic load. In the catalytic APR of SBW, TOC and COD removal was higher than 60% after reaction time of the experiments. The addition of KOH or NaOH to SBW resulted in a slightly lower TOC and COD removal, however higher yields to H2 and percentage of valuable gases were obtained in those cases where KOH was added. Catalyst with basic support and low contribution of micropores showed the best performance in the APR of SBW + KOH (∼50% of H2 and 8.9 mmol H2 /g COD). The concentration of anions detected in the liquid effluents varied with the catalysts tested and with the concentration of base, suggesting different reaction pathways. Increasing the concentration of KOH led to CO2 -free H2 without significant changes in H2 yield. The results obtained with RBW were in good agreement with those from SBW, although the significantly different behaviour of some catalysts suggests the need of tuning their properties according to the composition of the wastewater. Graphical abstract: Image 1 Highlights: Production of hydrogen from basic brewery wastewater is demonstrated. Addition of NaOH and KOH to brewery wastewater improves APR. Basic and mesoporous supports lead to higher production of gases and H2 . Higher H2 yield for KOH than for NaOH. CO2 -free H2 achievable by increasing the KOH concentration.